Hubungan Karakteristik dengan Kepatuhan Minum Obat Antidiabetes Pasien Diabetes Melitus di Pelayanan Kesehatan Kota Cirebon - Like Efriani (BORNEO JOURNAL OF PHARMASCIENTECH, 2022)
Characteristics and level of compliance are components that affect of diabetes mellitus (DM) therapy. The therapy of DM requires a level of compliance to succeed of controlling blood glucose levels in patients. Uncompliance to taking antidiabetic drugs causes blood glucose levels in the body to become uncontrolled. This study aims to see the correlation between patient characteristics and compliance to antidiabetic medication in DM patients in General Medical Center of Cirebon. The study was conducted by purposive sampling with a cross-sectional approach and using demographic data sheets to determine patient characteristics and the MMAS-8 (Morisky Medication Adherence Scale 8) questionnaire for medication compliance in DM patients. Respondents were selected based on inclusion and exclusion criteria. The results from respondents showed that the characteristics category of early elderly (46-55 years) has the highest percentage, followed by the female gender, and elementary school education (SD). Analysis showed that there was no significant correlation between characteristics based on age and compliance, but in the gender category and level of education, there was a significant correlation with compliance to taking antidiabetic medication in DM patients in General Medical Center of Cirebon.